Second-trimester maternal distress increases the risk of small for gestational age. Issue 13 (October 2014) - Khashan, A. S.; Everard, C.; McCowan, L. M. E.; Dekker, G.; Moss-Morris, R.; Baker, P. N.; Poston, L.; Walker, J. J.; Kenny, L. C.
<x content-type="archive" xml:space="preserve">Abstract</x> Background The effect of prenatal distress on the risk of a small for gestational age (SGA) infant is uncertain. We have addressed the influences of prenatal stress, anxiety and depression on the risk of SGA. We also examined the effects of infant sex and timing of distress during pregnancy on any observed associations. Method The study population comprised 5606 healthy nulliparous pregnant women who participated in the international prospective Screening for Obstetric and Pregnancy Endpoints (SCOPE) study. Women completed the Perceived Stress Scale (PSS), the short form of the Spielberger State–Trait Anxiety Inventory (STAI) and the Edinburgh Postnatal Depression Scale (EPDS) at 15 ± 1 and 20 ± 1 weeks' gestation. SGA was defined as birthweight below the 10th customized percentile. Logistic regression was used for data analysis, adjusting for several potential confounders such as maternal age, body mass index (BMI), smoking, socio-economic status and physical exercise. Results The risk of SGA was increased in relation to mild [adjusted odds ratio (aOR) 1.35, 95% confidence interval (CI) 1.07–1.71], moderate (aOR 1.26, 95% CI 1.06–1.49), high (aOR 1.45, 95% CI 1.08–1.95) and very high stress scores (aOR 1.56, 95% CI 1.03–2.37); very high anxiety score (aOR 1.45, 95% CI 1.13–1.86); and very high depression score (aOR 1.14, 95% CI 1.05–1.24) at 20 ± 1 weeks' gestation. Sensitivity analyses showed that very high anxiety and very high depression increases the risk of SGA in males but not in females whereas stress increases the risk of SGA in both males and females. Conclusions These findings suggest that prenatal stress, anxiety and depression measured at 20 weeks' gestation increase the risk of SGA. The effects of maternal anxiety and depression on SGA were strongest in male infants.